2020
DOI: 10.3390/cancers12071729
|View full text |Cite
|
Sign up to set email alerts
|

Basics and Frontiers on Pancreatic Cancer for Radiation Oncology: Target Delineation, SBRT, SIB Technique, MRgRT, Particle Therapy, Immunotherapy and Clinical Guidelines

Abstract: Pancreatic cancer represents a modern oncological urgency. Its management is aimed to both distal and local disease control. Resectability is the cornerstone of treatment aim. It influences the clinical presentation’s definitions as up-front resectable, borderline resectable and locally advanced (unresectable). The main treatment categories are neoadjuvant (preoperative), definitive and adjuvant (postoperative). This review will focus on (i) the current indications by the available national and interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 159 publications
(235 reference statements)
1
28
0
Order By: Relevance
“… 39 , 41 Additionally, it has been suggested that RT may have effects on the dense, immunosuppressive tumor microenvironment and stroma of PDAC in a way that increases immune cell response and antigen recognition. 42 This promising combination is currently being studied in a number of malignancies, 43 but has not been studied extensively in pancreatic malignancies. SBRT followed by durvalumab for pancreatic cancer is currently being studied in the metastatic setting in a Phase I trial; however, early data indicate poor therapy responses, with stable disease marking the best response in 21% of patients.…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 41 Additionally, it has been suggested that RT may have effects on the dense, immunosuppressive tumor microenvironment and stroma of PDAC in a way that increases immune cell response and antigen recognition. 42 This promising combination is currently being studied in a number of malignancies, 43 but has not been studied extensively in pancreatic malignancies. SBRT followed by durvalumab for pancreatic cancer is currently being studied in the metastatic setting in a Phase I trial; however, early data indicate poor therapy responses, with stable disease marking the best response in 21% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…For patients affected by locally advanced pancreatic cancer (LAPC), the first therapeutic approach is to date represented by combined systemic chemotherapy [ 3 , 4 , 5 ]. Treatment intensification with locoregional multimodal therapies such as high-intensity focused ultrasound (HIFU), chemoradiotherapy (CRT), or stereotactic body radiation therapy (SBRT) in patients showing stable disease or considered not resectable after chemotherapy induction is still a controversial issue in the oncological community [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SIB may be used to increase the fraction (and total) dose and BED to the boost volume, without lengthening the overall treatment time. This dose-painted strategy may be used to administer ablative doses to the hypoxic center of the pancreatic tumor, while the target area near critical OARs is covered by a safe dose (18). The anatomybased dose prescription strategy involves the radiobiological principle of fractionation (19).…”
Section: Introductionmentioning
confidence: 99%